Impact of COVID-19 pandemic on tuberculosis care and treatment in Puducherry - A mixed method study - Aparna Singh Yadav; Sonali Sarkar; Palanivel Chinnakali; Govindarajan Soundappan (Wolters Kluwer Medknow Publications, 2023)
Background: The shift of focus toward pandemic control had an impact on public health issues that need to be addressed. As the impact may vary in the different areas based on COVID-19 cases and strictness of measures to control the disease, studying the local situation and related factors is essential to strengthening the TB program. Objectives: The objective is to compare the TB care before and during the COVID-19 pandemic and to explore the challenges faced by stakeholders during the pandemic. Materials and Methods: A mixed method study was conducted in Puducherry with a quantitative phase involving data extraction from the National TB Elimination Programme (NTEP), followed by in-depth interviews to explore the challenges faced by stakeholders. Results: In 2020, there were 67% and 23% reductions in number of presumptive TB case and notified TB cases, respectively, while the decline was lesser in the year 2021 (reduction of 59% and 13%, respectively). The main challenges faced in providing and accessing TB care were social stigma, lockdown restrictions, fear of getting COVID-19, redeployment of staff to COVID-19-related activities and increased COVID-19 workload. Conclusions: There is a need to strengthen active case finding for the missed TB cases through the mobile vans equipped with diagnostics, combined testing for COVID-19 and TB, greater inclusion of private sector and dispensaries as well as community awareness for stigma prevention.